Pharmacokinetics and Pharmacodynamics with Extended Dosing of CC-486 in Patients with Hematologic Malignancies - Laille, Eric (PLoS One, 2015)
CC-486 (oral azacitidine) is an epigenetic modifier in development for patients with myelodysplastic syndromes and acute myeloid leukemia. In part 1 of this two-part study, a 7-day CC-486 dosing schedule showed clinical activity, was generally well tolerated, and reduced DNA methylation. Extending dosing of CC-486 beyond 7 days would increase duration of azacitidine exposure. We hypothesized that extended dosing would therefore provide more sustained epigenetic activity. Reported here are the pharmacokinetic (PK) and pharmacodynamic (PD) profiles of CC-486 extended dosing schedules in patients with myelodysplastic syndromes (MDS), chronic myelomonocytic leukemia (CMML) or acute myeloid leukemia (AML) from part 2 of this study. PK and/or PD data were available for 59 patients who were sequentially assigned to 1 of 4 extended CC-486 dosing schedules: 300mg once-daily or 200mg twice-daily for 14 or 21 days per 28-day cycle. Both 300mg once-daily schedules and the 200mg twice-daily 21-day schedule significantly (all P < .05) reduced global DNA methylation in whole blood at all measured time points (days 15, 22, and 28 of the treatment cycle), with sustained hypomethylation at cycle end compared with baseline. CC-486 exposures and reduced DNA methylation were significantly correlated. Patients who had a hematologic response had significantly greater methylation reductions than non-responding patients. These data demonstrate that extended dosing of CC-486 sustains epigenetic effects through the treatment cycle. TRIAL REGISTRATION: ClinicalTrials.gov NCT00528983